Literature review: Implementation of environmental ethics in the adiwiyata school program through adventure-based guidance in guidance and counseling services - Ambarwati (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Indonesia is a country blessed with abundant natural resources. Therefore, efforts to protect and preserve nature and the environment have become increasingly crucial. However, environmental problems continue to emerge as significant national and global issues, with waste management remaining one of the most pressing challenges. Education plays a central role in fostering environmental awareness among students, making schools an essential platform for developing ecological ethics and sustainable behavior. This study aims to elaborate on the concept of environmental ethics in education, analyze the implementation of environmental ethics within Adiwiyata Schools, and explain the contribution of Adventure-Based Guidance in Guidance and Counseling services to fostering students’ environmental awareness. Methods: The research employs a literature review method, synthesizing theoretical and empirical studies related to environmental education, experiential learning, and school counseling practices. Findings: The findings indicate that the integration of Adventure-Based Guidance within Guidance and Counseling services provides an innovative approach to environmental and character education. The Adventure-Based Guidance approach, rooted in experiential learning principles, allows students to learn through direct interaction with natural environments. Through activities such as outdoor counseling, adventure-based group guidance, and school-based environmental projects, students not only gain cognitive understanding of environmental issues but also develop affective and moral sensitivity toward nature. Counselors play a vital role in facilitating reflective sessions, transforming experiential learning into ethical awareness and moral responsibility for environmental preservation. Conclusion: The findings reveal that the implementation of Adventure-Based Guidance within Guidance and Counseling services significantly strengthens the Adiwiyata Program by fostering students’ ecological awareness, moral responsibility, and sustainable environmental character through experiential and reflective learning processes. Novelty/Originality of this article: This article offers a distinctive and interdisciplinary contribution to ecological education by integrating environmental ethics, school-based sustainability programs, and counseling psychology into a unified conceptual framework.